ANALISIS KEPUASAN PENGGUNA CAPCUT DAN KINEMASTER MENGGUNAKAN METODE END-USER COMPUTING SATISFACTION - Buana, Pratama Angga; Ardyan, Antonius Gilang; Tamboto, Fredrik Sebastian; Prakoso, Noer Hidayat; Yudistira, Danang Yunan; Derek, Gerri Wicaksana (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2025)
This study aims to analyze user satisfaction levels for the CapCut and KineMaster video editing applications using the End-User Computing Satisfaction (EUCS) approach. This research employed a descriptive quantitative method with data collected through questionnaires involving 67 respondents. The instrument's validity was tested using Pearson's Product Moment correlation, and reliability was assessed using Cronbach's Alpha method. The results show that CapCut excels in the Content (4.06), Accuracy (3.99), and Format (3.88) dimensions, while KineMaster leads in Ease of Use (3.52) and Timeliness (3.80). Overall, both applications achieved a Satisfied category in user satisfaction levels. This study provides strategic recommendations to improve the less dominant aspects of each application and serves as a reference for selecting video editing applications based on user needs.